The political transformation of Gulf tribal states : elitism and the social contract in Kuwait, Bahrain and Dubai, 1918-1970s - Yanai, Shaul (Sussex Academic Press, 2014)
This study details how the reform movements and attempts to establish parliamentary institutions in the Persian Gulf states of Kuwait, Bahrain, and Dubai between the First World War and the independent era of the 1970s represented a milestone in the history of the region, creating a legacy for future generations, but was a unique transition in the Arab world. An important work to understanding the history of the Persian Gulf states, the book illustrates how, as this new political and social order evolved, ideas of national struggle and national rights penetrated Gulf societies. Gulf citizens w.